Detection of Malaria Parasites in Different Age and Gender Groups Using a Light Microscopy - Muhammad Asif Zeb, Muhammad Irshad, Syed Abbas Anwar, Dur-E-Nayyab, Muhammad Ibrahim, Muhammad Zubair (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Malaria is the world’s most frequent tropical infectious illness and serious public health concern in Pakistan. Malaria prevention in tropical regions depends on effective Plasmodium infection diagnosis. The purpose of this study was to use microscopy to determine the prevalence of malaria in various age and gender categories. Materials and Methods: A cross-sectional study of 1000 people was undertaken to detect malaria. Thick and thin blood smears were prepared and stained with freshly made Giemsa stain before being examined under a light microscope. Results: Malaria parasites were identified in 40.3% of the total number of suspected cases. The age group 41-60 years had the highest proportion of malaria-infected people (45.1%), whereas the age group >60 years had the lowest proportion (21.7%). Males were found to be more affected, accounting for 45.7% of the total 525 people, while females accounted for 34.3% of the total 475 people. Conclusion: It has been determined that malaria parasites infected more adults and males than children and females. In developing regions, light microscopy is the sole feasible method for malaria diagnosis. Accurate malaria diagnostic procedures have a significant impact on reducing the number of malaria-infected people. As a result, reinforcing microscopist training is critical for establishing accurate malaria diagnoses. Keywords: Malaria, Light Microscope, Plasmodium, Pakistan